Output-series modular DC-DC converter with self-voltage balancing for integrating variable energy sources - Sun, Changjiang (2022)
Due to its high voltage boost capability, the output-series modular dc-dc converter (OSMDC) system with multiple independent inputs is a promising solution for the integration of distributed renewable energy. However, the unequal power injection among the variable energy sources (VESs) makes the module voltage balancing at the output stage a crucial issue for OSMDC. To solve this issue, this letter presents a new OSMDC topology based on the promising semi-dual active bridge (SDAB) converter module. Embedded non-isolated resonant dual active bridge (NRDAB) converters are constructed between the adjacent modules by adding LC branches to link the load-side active-leg midpoints of the SDABs. This configuration facilitates self-voltage balancing among the modules and retains zero-voltage switching (ZVS) characteristics of SDAB. The lab-scale experiment has been conducted to verify the operating principles and performance of the proposed OSMDC.